The technique of laparoscopic and robotic extended cholecystectomy for gallbladder cancer - Kwang Hyun Kim; Tinna Osk Thrastardottir; Sung Hoon Choi (Journal of Minimally Invasive Surgery)
The application of minimally invasive surgery for gallbladder cancer (GBC) is yet controversial. This article discusses the techniques of laparoscopic and robotic extended cholecystectomy. A 69-year-old male diagnosed with cT1-2N0 GBC underwent laparoscopic surgery, and a 55-year-old male with cT2N1 GBC underwent robotic surgery after preoperative chemotherapy. Nonanatomical partial hepatectomy with lymphadenectomy was performed. Liver parenchymal dissection was performed using Cavitron Ultrasonic Surgical Aspirator laparoscopically and Maryland bipolar dissector and Harmonic scalpel robotically. The operation time was 180 and 220 minutes, and the estimated blood loss was 140 and 130 mL, respectively. The final pathologies were pT1bN0 and pT2aN1, for which patients received adjuvant chemotherapy. There was no evidence of recurrence at 33 and 18 months without complications. Both laparoscopic and robotic extended cholecystectomy can be safely performed with the robotic surgical system as an effective alternative for GBC requiring liver resection with radical lymphadenectomy.